The Approach To The Administrative Mapping In Knowledge Management For Portugal Libraries - Caldas, Rosangela Formentini [UNESP] (Int Business Information Management Assoc-ibima, 2011)
In the study of theoretical trends in Administration, the management of information follows the development of theories of Administration; constant-adaptations are suffered. Information Science as Museums, Archives and Libraries, understands and concerns itself with the changes wrought in these endeavour of the knowledge society as new forms of communication and integration. They interact in ways such as to maximize access to information and facilitate improvement on their structural environment. The research aims at identifies the requirements and specifications of an information system for knowledge management in the public's library enviromnent and proposes to achieve a pre-defined structure for the implementation of administration management. The research is conducted with public's library of the metropolian region of the North's Portugal. In the improvement of systems theoretical administrative trends become management decisions and result in the ultimate success of the organization.
Keywords: Organizational Theory; Knowledge Management; Public's library